2017
DOI: 10.1007/s11060-017-2587-5
|View full text |Cite
|
Sign up to set email alerts
|

Volumetric quantification of glioblastoma: experiences with different measurement techniques and impact on survival

Abstract: The potential impact of different radiological features of glioblastoma multiforme (GBM) on overall survival (OS) like tumor volume, peritumoral edema (PTE), necrosis volume, necrosis-tumor ratio (NTR) and edema-tumor ratio (ETR) is still very controversial. To determine the influence of volumetric data on OS und to compare different measuring techniques described in literature. We prospectively evaluated preoperative MR images from 30 patients harboring a primary supratentorial GBM. All patients received gros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
48
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(54 citation statements)
references
References 42 publications
5
48
1
Order By: Relevance
“…Age, performance status, extent of surgical resection and MGMT methylation status are well known prognostic factors for GBM patients [4,[21][22][23][24][25][26][27][28][29][30][31][32][33][34][39][40][41][42][43][44]. Nevertheless, the high degree of clinical/molecular heterogeneity found among GBM patients do not generally allow us to correctly classify GBM patients with the use of a single predictor or a few predictors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Age, performance status, extent of surgical resection and MGMT methylation status are well known prognostic factors for GBM patients [4,[21][22][23][24][25][26][27][28][29][30][31][32][33][34][39][40][41][42][43][44]. Nevertheless, the high degree of clinical/molecular heterogeneity found among GBM patients do not generally allow us to correctly classify GBM patients with the use of a single predictor or a few predictors.…”
Section: Discussionmentioning
confidence: 99%
“…To classify GBM cases according to this heterogeneity, different prognostic factors have been suggested for GBM, including age, performance status, specific molecular markers [e.g., MGMT methylation (O 6 -methylguanine-DNA methyl-transferase), mutation of IDH1, IDH2(isocitrate dehydrogenase) or TERT (telomerase reverse transcriptase), 1p19q codeletion, overexpression of EGFR (epidermal growth factor receptor)], the size of necrosis and the extent of resection (EOR) [15][16][17][18][19][20][21][22]. The role of EOR in improving survival in patients with GBM has widely been demonstrated, with more extensive resections providing added advantages [8,9,16,18,19,[23][24][25][26][27][28][29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…Present results confirm that, the higher the volume of the FLAIR-T 2 image, the worse the prognosis is. However, there is some controversy in this respect, since some studies have shown correlations between FLAIR-T 2 hyper-intensities with longer OS ( 13 18 , 40 , 47 ), while others have not been able to prove it ( 12 , 13 , 48 , 49 ). Many factors, including the non-exclusion of cystic cavities, the influence of corticosteroid treatment, and the inclusion of both, IDH-mutated, and IDH wild-type tumors, may further underlie these discrepancies.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, OS and PFS in glioblastomas have been previously associated to various compartmental tumor volumes including: the volume of necrosis ( 12 14 ), the volume of contrast-enhancing tumor ( 11 ), the volume of FLAIR-T 2 hyper-intensity ( 13 18 ), or the tumor/necrosis volume ratio ( 13 , 19 ). Unfortunately, results and conclusions from many of these studies remain contradictory.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation